Pioglitazone alleviates inflammation in diabetic mice fed a high‐fat diet via inhibiting advanced glycation end‐product‐induced classical macrophage activation. (9th May 2016) - Jin, Xian; Liu, Liang; Zhou, Zhong'e; Ge, Junhua; Yao, Tongqing; Shen, Chengxing
Abstract : Classically activated macrophages (M1) are associated with inflammation in diabetic patients. Inflammation is a known risk factor in diabetes. The present study tested the hypothesis that pioglitazone (PIO) alleviates inflammation in diabetic mice fed a high‐fat diet by inhibiting advanced glycation end‐product (AGE)‐induced classical macrophage activation. It was found that AGE treatment promoted the transcription of pro‐inflammatory molecules and M1 surface markers, whereas PIO increased the expression of anti‐inflammatory genes and decreased the expression of pro‐inflammatory mediators in bone marrow‐derived macrophages (BMDMs) in a dose‐dependent manner. Furthermore, pretreatment with PIO abrogated the effects of AGE on pro‐inflammatory markers and partly inhibited AGE‐induced nuclear factor‐κB (NF‐κB) activation. PIO treatment partly reduced the inflammatory phenotype in diabetic ApoE −/− mice, and significantly reduced NF‐κB activation in plaques. Therefore, we conclude that PIO blocks classical activation of macrophages and attenuates inflammation in mouse models of diabetes. Abstract : We found that advanced glycation end product (AGE) promote inflammation by enhanced macrophage polarization into an M1 phenotype. Pioglitazone (PIO) inhibited AGE‐induced classical macrophage polarization in a mouse model of diabetes via PPARγ‐dependent inactivation of NFκB. Such effects of pioglitazone improved the M1/M2 imbalance in diabetes and attenuated diabetic inflammation. The present study provided fresh insight into pioglitazone's anti‐inflammatory properties.